Total Occlusion of the Abdominal Aorta Caused by Detachment of Cardiac Myxoma - Hong, Sungyong (Korean Society for Thoracic and Cardiovascular Surgery, 2012)
Abdominal aortic occlusion (AAO) caused by detachment of cardiac myxoma (CM) is a very rare complication in patients with CM. Although the nature of CMs has been well established, detachment of CM may cause unexpected serious complications such as vicious embolic events. Actually, in several cases of AAO caused by detachment of CM, it has been reported that CM fragments easily migrated to the brain, heart, and lungs, and caused lifelong neurological complications despite appropriate surgical therapy. Herein, we report a case of a patient with AAO caused by detachment of CM who underwent CM excision and abdominal aortic thromboembolectomy. Additionally, we have presented the preoperative and postoperative images using 64-multidetector computed tomography.